Uso de los Sistemas informáticos aplicados en la agricultura de precisión en cultivos de caña de azúcar - Ortega Moran, Christian Alexander (2022)
SUMMARY This research has a descriptive and bibliographic nature, the sources of information were scientific publications and digital documents directly related to the research topic: "Use of computer systems applied in precision agriculture in sugarcane crops", the primary objective is to identify the technologies used in this crop. Technological advances contribute to the development of humanity, within these ICTs (information and communication technologies) have been used in various crops worldwide. Its use is closely related to precision agriculture, because it allows us to monitor the state of the crop, the use of inputs, and the yield per hectare. Sugarcane is one of the crops that takes advantage of these technologies. Once the data has been analyzed, it is concluded that precision agriculture, despite its multiple benefits, is not being applied by small and medium-sized producers. Based on this, it is recommended that research be increased and that an agricultural technological innovation plan be implemented that allows access to the use of ICTs by implementing the use of GPS, remote sensors, GIS programs, mapping and production indices, the use of the SAGA system. The use of IoT ((Internet of Things) facilitates the remote analysis of crop data and optimizes the use of resources through teleworking.